Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 6 - Section 6.3 - Equations with Parentheses - Exercises: 40

Answer

y=-4

Work Step by Step

Simplifying 2(y + -3) = 4 + (y + -14) Reorder the terms: 2(-3 + y) = 4 + (y + -14) (-3 * 2 + y * 2) = 4 + (y + -14) (-6 + 2y) = 4 + (y + -14) Reorder the terms: -6 + 2y = 4 + (-14 + y) Remove parenthesis around (-14 + y) -6 + 2y = 4 + -14 + y Combine like terms: 4 + -14 = -10 -6 + 2y = -10 + y Solving -6 + 2y = -10 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -6 + 2y + -1y = -10 + y + -1y Combine like terms: 2y + -1y = 1y -6 + 1y = -10 + y + -1y Combine like terms: y + -1y = 0 -6 + 1y = -10 + 0 -6 + 1y = -10 Add '6' to each side of the equation. -6 + 6 + 1y = -10 + 6 Combine like terms: -6 + 6 = 0 0 + 1y = -10 + 6 1y = -10 + 6 Combine like terms: -10 + 6 = -4 1y = -4 Divide each side by '1'. y = -4 Simplifying y = -4
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.